1976
DOI: 10.1037/0096-1523.2.2.210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of concurrent verbal memory on recognition of stimuli from the left and right visual fields.

Abstract: Two experiments examined the effect of concurrently holding 0, 2, 4, or 6 nouns in memory on the recognition of visual stimuli briefly presented to the left or right visual fields. When stimuli to be visually recognized were complex visuospatial forms it was found that a relatively easy memroy load of 2 or 4 nouns improved visual recognition accuracy on right visual field (left-hemisphere) trials relative to the no-memory condition; however, a more difficult memory load of 6 nouns decreased visual recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
2
1

Year Published

1978
1978
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 17 publications
8
90
2
1
Order By: Relevance
“…The left-hemisphere advantage for these studies could have arisen from the subject's attempts to maintain the positive set by rehearsing the names or labels of the items. This effect has been reported by Hellige and Cox (1976), who found a strong left-hemisphere advantage for the recognition of verbal stimuli when subjects were concurrently rehearsing additional verbal items.…”
Section: Discussionmentioning
confidence: 65%
“…The left-hemisphere advantage for these studies could have arisen from the subject's attempts to maintain the positive set by rehearsing the names or labels of the items. This effect has been reported by Hellige and Cox (1976), who found a strong left-hemisphere advantage for the recognition of verbal stimuli when subjects were concurrently rehearsing additional verbal items.…”
Section: Discussionmentioning
confidence: 65%
“…in a dual-task paradigm, one might have hypothesized that the engagement of a concurrent memory load would impair (rather than enhance) performance on the primary Mr task, a hypothesis suggested by Moore (2003) and others (e.g., Pelligrino, Siegal, & Dhawan, 1975;Warren, 1977), particularly if the secondary activity is similar in nature to the processing required to perform the primary task. However, considerable research suggests that a relatively low-demand concurrent activity can actually prime performance on a primary task because it increases cognitive arousal, which in turn provides additional processing resources that can subsequently be allocated to the processing of the primary task; this results in enhanced (rather than impaired) primary task performance (Hellige, 1993;Hellige & cox, 1976;Kinsbourne, 1973Kinsbourne, , 1975Kinsbourne, 1975;Kinsbourne & cook, 1971;Kinsbourne & Hicks, 1978a;Kinsbourne & Hicks, 1978b;O'Boyle et al, 1987). the fact that Mr performance in our study was better in both the verbal and spatial load conditions as compared with the no-load condition supports the idea that a mildly demanding concurrent memory load actually primes rather than impairs Mr performance.…”
Section: Discussionmentioning
confidence: 99%
“…Hemisphere of input did not interact significantly with target or probe type , indicating faster left-hemisphere processing for both words and pictures. Several studies (e.g., Hellige & Cox, 1976 ;Kinsbourne, 1975) have shown that a concurrent verbal memory load influences laterality types for word targets, but reaction time to picture probes was significantly faster than word probes for picture targets . Paivio (1976) has proposed a dual coding model of memory encoding , in which it is postulated that material is encoded and can be retrieved in both .…”
Section: Hemispheric Dominance and Lateralitymentioning
confidence: 99%